2006
DOI: 10.1260/147547206779379877
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the PSE Approach for Subsonic and Supersonic Hot Jets. Detailed Comparisons with LES and Linearized Euler Equations Results

Abstract: A Parabolized Stability Equation (PSE) method is applied to hot inviscid Mach 0.7 and Mach 2 axisymmetric jets. The Parabolized Stability Equations are derived from the linearized Euler equations. Spatial development of pressure perturbations is computed in the vicinity of the jet, and the associated radiated noise is obtained by solving the wave equation. A Large Eddy Simulation is performed on the subsonic jet and compared with the results obtained by the PSE analysis of the LES-computed mean flow. Good agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…This eigenmode decomposition can be achieved by making use of the bi-orthogonality between the eigenfunctions of the direct and adjoint LST problems. [21][22][23] The approach of modeling wave packets as linear instability waves has been widely employed in the study of forced supersonic jets, 5,10,12,[24][25][26] for which the measured near-field fluctuations were found to be in good agreement with the predictions of linear stability theory. 9 In the case of subsonic natural jets, this approach has only recently begun to deliver satisfactory quantitative predictions, both in the near pressure and velocity fields.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…This eigenmode decomposition can be achieved by making use of the bi-orthogonality between the eigenfunctions of the direct and adjoint LST problems. [21][22][23] The approach of modeling wave packets as linear instability waves has been widely employed in the study of forced supersonic jets, 5,10,12,[24][25][26] for which the measured near-field fluctuations were found to be in good agreement with the predictions of linear stability theory. 9 In the case of subsonic natural jets, this approach has only recently begun to deliver satisfactory quantitative predictions, both in the near pressure and velocity fields.…”
Section: -3mentioning
confidence: 99%
“…A further improvement in the linear model can be achieved with the introduction of ad hoc eddy viscosity models. [5][6][7] Following diverse assumptions on the characteristics of the mean flow and wave packets, different approaches to the computation of instability waves have been employed in the past, including locally parallel stability analysis based on the Orr-Sommerfeld equation, 8 multiple-scales analysis, 4,9 parabolized stability equations (PSE), [10][11][12][13] global eigenmode analysis, 14 and boundaryvalue problems. 15 Independent of the particular approach followed for the wave packet modeling, the governing equations are deterministic and the solution depends on prescribed inlet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling of wavepackets in unforced jets was also attempted (e.g. Tam & Chen 1994;Balakumar 1998;Yen & Messersmith 1998;Piot et al 2006), but this was hampered owing, in hindsight, to a lack of detailed spatiotemporal data. Furthermore, none of these studies showed how a linear instability wave could be consistent with the fluctuations of a real turbulent jet.…”
Section: Introductionmentioning
confidence: 99%
“…There were many attempts to validate this theory that were viewed as successful (e.g. Troutt & McLaughlin 1982;Tam & Hu 1989;Tam & Chen 1994;Balakumar 1998;Yen & Messersmith 1999;Lin et al 2004;Piot et al 2006), and the earlier efforts were reviewed by Tam (1991Tam ( , 1995. However, the comparisons were actually based on limited measurements, and the lack of consistent identification of both the near and far sound fields prevented a more rigourous test of the theory.…”
Section: Introductionmentioning
confidence: 99%
“…First, we employ parabolized stability equations (PSE), introduced by Bertolotti & Herbert (1991). This approach represents a refinement of the locally parallel approach whereby both nonparallel and nonlinear effects can be retained in the analysis of slowly spreading, convectively unstable flows such as boundary layers (Bertolotti & Herbert 1991;Bertolotti, Herbert & Spalart 1992;Chang et al 1993), planar mixing layers (Day, Mansour & Reynolds 2001;) and jets (Balakumar 1998;Yen & Messersmith 1998;Malik & Chang 2000;Piot et al 2006;Gudmundsson & Colonius 2009;Ray & Cheung 2009). While it is computationally feasible nowadays to perform a global stability analysis of the jet mean flow field (Chomaz 2005), we prefer PSE with an eye towards developing rapidly computable, reduced-order models for the farfield sound associated with large-scale structures (Colonius, Samanta & Gudmundsson 2010;Reba, Narayanan & Colonius 2010).…”
Section: Introductionmentioning
confidence: 99%